MoleculARweb: a web site for chemistry and structural biology education through interactive augmented reality out of the box in bommodity devices - Cortés Rodríguez, Fabio (2021)
Fil: Fil: Cortés Rodríguez, Fabio. Escuela Politécnica Federal de Lausana. Instituto Suizo de Bioinformática. Laboratorio de Modelado Biomolecular. Suiza.